2022
DOI: 10.1101/gr.275509.121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transcript enrichment and detection bias in single-nucleus RNA-seq for mapping of distinct human adipocyte lineages

Abstract: Single-cell RNA sequencing (scRNA-seq) enables molecular characterization of complex biological tissues at high resolution. The requirement of single-cell extraction, however, makes it challenging for profiling tissues such as adipose tissue, for which collection of intact single adipocytes is complicated by their fragile nature. For such tissues, single-nucleus extraction is often much more efficient and therefore single-nucleus RNA sequencing (snRNA-seq) presents an alternative to scRNA-seq. However, nuclear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 120 publications
3
44
0
Order By: Relevance
“…Other studies have shown differences in sn and sc RNAseq data that may contribute differences in our dataset and others. 6, 50 Indeed the higher degree of concordance of our data with that of Emont et al, who performed snRNASeq, compared with Vijay et al, who used scRNASeq, support such differences. In addition, while some studies such as Vijay et al suggest a larger number of human ASC subtypes than our current data, few of their computationally defined types have been experimentally or functionally validated.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Other studies have shown differences in sn and sc RNAseq data that may contribute differences in our dataset and others. 6, 50 Indeed the higher degree of concordance of our data with that of Emont et al, who performed snRNASeq, compared with Vijay et al, who used scRNASeq, support such differences. In addition, while some studies such as Vijay et al suggest a larger number of human ASC subtypes than our current data, few of their computationally defined types have been experimentally or functionally validated.…”
Section: Discussionsupporting
confidence: 76%
“…Single-cell RNA sequencing (scRNAseq) data in mice and humans confirm significant heterogeneity of the AT cellular landscape and identify multiple functionally distinct populations of adipocyte progenitor cells (preadipocytes), immune cells, and other cell types. [1][2][3][4][5][6] This cellular diversity has important implications for an understanding of obesity and metabolic disease pathophysiology and development of translational therapy. scRNAseq methodology has numerous limitations for analysis of AT, including the requirement for collagenase digestion of tissue, which may alter the transcriptome and eliminate cell subpopulations, the inability to capture large, fragile mature adipocytes which are disrupted by microfluidic sorting, and the inability to study banked, frozen samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Gupta et al 2022 introduced a normalization scheme designed to account for discrepant gene length bias in cell-vs-nucleus comparisons 21 . Specifically, they propose separating total transcript counts (i.e., observed UMIs per gene per cell) into exon - and intron -derived components and scaling solely the intron UMI counts by gene length multiplied by the transcriptome-wide rate of internal priming site occurrence ( Figure 1C ).…”
Section: Introductionmentioning
confidence: 99%